Production Constraints and the NAIRU - Stephen G. Hall; Ciaran F. Driver (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
This paper argues that the production constraints in the basic NAIRU model should be distinguished by type: capital constraints and labour constraints. It notes the failure to incorporate this phenomenon in standard macro models. Using panel data for UK manufacturing over 80 quarters we show that capital constraints became relatively more important during the 1980s as industry failed to match the increase in labour flexibility with rising capital investment.
Keywords: C23; D24; E22; E24; 330; Capital; labour; constraints; NAIRU; panel data; structural breaks; Natürliche Arbeitslosigkeit; Kapitalproduktivität; Arbeitsproduktivität; Panel; Strukturbruch; Verarbeitendes Gewerbe; Großbritannien